Electrochemical behavior of a membrane based on zirconium(iv) phosphoborate nanocomposite and its application in dye removal. Issue 112 (24th November 2016) - Kaushal, Sandeep; Badru, Rahul; Kumar, Sanjeev; Sharma, Pushpender K.; Mittal, Susheel K.; Singh, Pritpal
Abstract : A new hybrid ion-exchange membrane was prepared from a novel composite obtained by dispersion of polyaniline into an inorganic matrix of zirconium(iv ) phosphoborate employing a sol–gel method. Abstract : A new hybrid ion-exchange membrane was prepared from a novel composite obtained by dispersion of polyaniline into an inorganic matrix of zirconium(iv ) phosphoborate employing a sol–gel method. The composite was characterized by FTIR, XRD, SEM, TEM and TGA/DTA analysis. Membrane potential, transport number, permselectivity and fixed charge density were studied as a function of electrolytic concentration, in order to explore the electrochemical behavior of the prepared membrane. Values for all these electrochemical properties were found to increase upto a mean concentration for each electrolyte and declined thereafter. All these electrochemical properties have higher values for monovalent alkali metal cations than those for bivalent alkaline earth metal cations. The nanocomposite worked well to hamper the growth of both G − and G + bacterial cultures of Escherichia coli and Bacillus strains to a remarkable level. The nanocomposite was also evaluated for adsorptive removal of methylene blue from aqueous solutions. Maximum adsorption was achieved at pH 11 with an adsorbent dosage of 20 mg for a 1.6 mg/100 mL dye solution in an interval of 3.5 h. Up to 99% dye was recovered upon elution and the regenerated column was efficiently used a number of times. Promising results obtained in dye removal by adsorption and antimicrobial activity encourage the use of such composites in water purification.